Farmers’ perception about importance of phenotypic characters in pricing of a buffalo - DIXIT, V B; BHARADWAJ, A; SINGH, K P; DUHAN, A; TRIPATHI, HEMA (The Indian Journal of Animal Sciences, 2016)
The study was conducted in Haryana and the response of 240 farmers was elicited on 18 phenotypic characters regarding their perception about the importance of these characters in fixing the price of a buffalo. On the basis of their mean scores, ranks were calculated in both the categories of villages. The study revealed that milk yield (4.96), parity (4.42) and stage of lactation were considered the most important in (category 1) villages while milk yield (4.84), shape and size of udder (4.14) and parity (4.06) were perceived as the most important in category 2 villages in determining the price of a buffalo. Rho-value of 0.87 indicated that there was association in their responses regarding the role of phenotypic characters in determining their price. Results pertaining to stepwise-forward regression indicated that 6 phenotypic characters contributed to the extent of 88% in deciding the price of a buffalo.